Protocol and statistical analysis plan for the mega randomised registry trial comparing conservative vs. liberal oxygenation targets in adults with nonhypoxic ischaemic acute brain injuries and conditions in the intensive care unit (Mega-ROX Brains) - Young, Paul J.; Al-Fares, Abdulrahman; Aryal, Diptesh; Arabi, Yaseen M; Ashraf, Muhammad Sheharyar; Bagshaw, Sean M.; Mat Nor, Mohd Basri; Beane, Abigail; Borghi, Giovanni; de Oliveira Manoel, Airton L.; Dullawe, Layoni; Fazla, Fathima; et al. (Elsevier, 2023)
Background: The effect of conservative vs. liberal oxygen therapy on 90-day in-hospital mortality in adults who have nonhypoxic ischaemic encephalopathy acute brain injuries and conditions and are receiving invasive mechanical ventilation in the intensive care unit (ICU) is uncertain. Objective: The objective of this study was to summarise the protocol and statistical analysis plan for the Mega-ROX Brains trial. Design, setting, and participants: Mega-ROX Brains is an international randomised clinical trial, which will be conducted within an overarching 40,000-participant, registry-embedded clinical trial comparing conservative and liberal ICU oxygen therapy regimens. We expect to enrol between 7500 and 9500 participants with nonhypoxic ischaemic encephalopathy acute brain injuries and conditions who are receiving unplanned invasive mechanical ventilation in the ICU. Main outcome measures: The primary outcome is in-hospital all-cause mortality up to 90 d from the date of randomisation. Secondary outcomes include duration of survival, duration of mechanical ventilation, ICU length of stay, hospital length of stay, and the proportion of participants discharged home. Results and conclusions: Mega-ROX Brains will compare the effect of conservative vs. liberal oxygen therapy regimens on 90-day in-hospital mortality in adults in the ICU with acute brain injuries and conditions. The protocol and planned analyses are reported here to mitigate analysis bias. Trial Registration: Australian and New Zealand Clinical Trials Registry (ACTRN 12620000391976).